Synthesis and in vitro evaluation of new oxadiazole thioethers as antibacterials - Ali H. Abbas (Pharmacia)
A study was conducted to synthesize a new set of compounds named comp.4–7 using the 1,3,4 tautomer of oxadiazole as the centroid unit. These compounds were subjected to various characterization processes, including thin-layer chromatography, infrared spectroscopy, and 1HNMR spectroscopy. The study was based on previous research that established several compounds’ diverse range of biological activities, such as hydrazide Schiff’s bases (hydrazones), oxadiazoles, thiophenes, and isoxazoles. These compounds had been found to possess properties against bacteria, fungi, TB, viruses, cancer cells, and inflammatory responses, as well as analgesic properties. The results of the docking study were conducted in MOE software, targeting the largest binding site of E. coli gyrase B (PDB: 6YD9) as identified by SITE FINDER, suggesting that these compounds had great potential to be effective antibacterial agents. To evaluate the synthesized compounds antibacterial activities, the well diffusion method was used, and the findings revealed that the synthesized compounds exhibit slight to moderate activities against E. coli, S. aureus, and K. pneumoniae.